1992
DOI: 10.1099/0022-1317-73-9-2327
|View full text |Cite
|
Sign up to set email alerts
|

Analysis by polymerase chain reaction of the physical state of human papillomavirus type 16 DNA in cervical preneoplastic and neoplastic lesions

Abstract: Integration of human papillomavirus (HPV) DNA into the host cell genome is believed to be essential for malignant progression. However unambiguous detection of the physical state of HPV is a difficult and timeconsuming procedure. To resolve this issue a simple, rapid and highly sensitive technique of polymerase chain reaction (PCR) has been utilized for detecting the physical state of HPV-16 DNA. Investigations were carried out in 122 cervical specimens comprising the whole spectrum of cervical lesions startin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
120
3
8

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(139 citation statements)
references
References 37 publications
8
120
3
8
Order By: Relevance
“…Papillomavirus E2 proteins were reported to down-regulate the major early promoters of genital HPVs involved in the transcription of the E6 and E7 oncogenes. On the other hand, the E1 and\or E2 gene regions of oncogenic HPV types were shown to be inactivated through integration of the viral genome into host DNA, which is a frequent event in carcinogenesis (Das et al, 1992). It was suggested that this mechanism has a major role in the up-regulation of the early HPV promoters in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Papillomavirus E2 proteins were reported to down-regulate the major early promoters of genital HPVs involved in the transcription of the E6 and E7 oncogenes. On the other hand, the E1 and\or E2 gene regions of oncogenic HPV types were shown to be inactivated through integration of the viral genome into host DNA, which is a frequent event in carcinogenesis (Das et al, 1992). It was suggested that this mechanism has a major role in the up-regulation of the early HPV promoters in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The E2 ORF was amplified from HPV-16-positive cervical cancer specimens by PCR using the primers E2\1 (5h GCGCGAATCCAGGACGAGGACAAGGAAAA 3h ; nt 2735-2753) and E2\2 (5h GCGCGAATCCGGATGCAGTATC-AAGATTTG 3h ; nt 3854-3873) (artificial EcoRI sites used for cloning in both primers are underlined). In this PCR, a 1139 bp long amplimer was produced, which included the whole E2 gene (Das et al, 1992). Amplification was performed with Pwo polymerase (an enzyme with proof-reading activity), according to the manufacturer's recommendations (Boehringer Mannheim).…”
Section: Methodsmentioning
confidence: 99%
“…A gene fragment of the b-globin was used as an internal control to check the integrity of the specimens. Further HPV typing was carried out using type-specific primers for HPV types 16, 18, 6 and 11 (Das et al, 1992a). Polymerase chain reaction products were separated electrophoretically on an ethidium bromide stained 3% Nusieve agarose gel.…”
Section: Hpv Analysismentioning
confidence: 99%
“…Polymerase chain reaction (PCR) for the URR, E6, E2 and E4 genes were carried out as published by May et al, 11 Wheeler et al 12 and Das et al, 13 respectively. The controls used and the precautions taken to minimize the possibility of cross-contamination of specimens at all stages of processing were as previously published.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
“…13 The specificity of the E2 PCR products was confirmed either by sequencing or by cleavage with Hinc II to produce bands of 662 bp and 476 bp.…”
Section: E2 Pcr For Determination Of the Physical Statementioning
confidence: 99%